Examining the Role of Teachers’ Stroking Behaviors in EFL Learners’ Active/Passive Motivation and Teacher Success - Pishghadam, Reza; Derakhshan, Ali; Jajarmi, Haniyeh; Tabatabaee Farani, Sahar; Shayesteh, Shaghayegh (Frontiers in Psychology, 2021)
Due to the important role that teachers’ professional success plays in the effectiveness of their ‎students and the education system in which they are involved, the present study investigated ‎whether teacher stroke can predict teacher success through the mediation of students’ active ‎and passive motivation. For this aim, a group of 437 Iranian university English as a Foreign ‎Language (EFL) students were targeted to respond to the teacher success, teacher stroke, and ‎student motivation questionnaires. The main results of the study, obtained through running ‎correlation and structural equation modeling (SEM), were first, while positive stroke showed ‎a positive correlation with teacher success, it did not directly predict success; yet mediated by ‎active motivation, it was a positive predictor of success; second, while teacher success had no ‎significant relationship with total motivation, it was positively correlated with active and ‎passive motivation, separately; third, in terms of gender differences, for the female ‎participants, stroke, mediated by active motivation, was a better predictor of teacher success; ‎fourth, high scores in positive, verbal, and conditional stroke were in association with high ‎scores in active motivation, which significantly predicted teacher success. Based on the ‎results, it can be concluded that teacher stroke, as an instance of positive teacher interpersonal ‎communication behaviors, increases students’ active motivation for foreign language learning, ‎which in turn results in their higher perceptions of English teachers’ professional success. ‎